Hubungan berat badan lahir, pemberian ASI eksklusif, status gizi dan stimulasi kognitif dengan kecerdasan anak usia 5–6 Tahun - Rini Andarwati; Endy Paryanto Prawirohartono; Indira Laksmi Gamayanti (Minat S2 Gizi dan Kesehatan, Prodi S2 IKM, FK-KMK UGM, 2006)
Background: Intellegence is affected by 2 factors, internal (genetics) and external (nutrition intake, infection, toxin, stimu- lation, environmental) factors. Sufficient nutrition is very important during pregnancy. Birth weight and exclusive breastfeeding affect brain growth and development. Malnutrition during infancy results in stunting and impaired cognitive function in children. Lack of stimulation may affect intelligence.Objective: The objective of the study was to find out the relationship among birth weight, exclusive breastfeeding, nutrition status and cognitive stimulation and intelligence.Method: An analytic observational study was conducted with cross sectional design, at kindergarten in Prambanan Subdistrict. Subjects were recruited based on a cluster random sampling technique. There were 50 children and mothers met the inclusion criteria of mothers who knew the child’s background (birth weight, breastfeeding practices) and were willing to be included in this study. Intelligence was assessed using Stanford Binet test. Data were analyzed with chi square and logistic regression tests.Results: The study showed that 76% of children had normal intelligence and 24% of children had abnormal intelligence. Based on multivariable analysis, low cognitive stimulation was a risk factor of getting low IQ score (OR=15.6; CI 95%=1.725– 141.272), whereas birth weight (OR=1.1; CI 95%=0.126– 9.751), exclusive breastfeeding (OR=4.9; CI 95%=0.494– 49.054) and nutrition status did not relate to intelligence.Conclusion: There was significant relationship between cognitive stimulation and intelligence, whereas birth weight, exclusive breastfeeding and nutrition status did not significantly relate with intelligence.